HLA-G regulation through trogocytosis: intercellular membrane transfer mechanisms and immune dysregulation in Systemic Lupus Erythematosus - Karmakar, Abhibroto; Kumar, Uma; Kamath, Rachana; Singh, Hargurdas; Prabhu, Mukhyaprana M.; Karmakar, Subhradip (Frontiers in Cell and Developmental Biology, 2025)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder marked by dysregulated humoral immunity, autoantibody production against nuclear and cytoplasmic antigens, and immune complex deposition that triggers widespread inflammation and tissue damage. Central to its pathogenesis are breakdowns in peripheral tolerance, aberrant T and B cell activation, and chronic type I interferon signalling, driving the disease’s heterogeneity. Emerging evidence highlights trogocytosis, a process involving the direct transfer of membrane-associated molecules between immune cells as a key immunomodulatory mechanism in autoimmunity. Through bidirectional membrane exchange, trogocytosis alters the surface receptor landscape, antigen presentation, and signalling capacity of immune cells without requiring new protein synthesis. In SLE, trogocytosis has been linked to the dysregulation of HLA-G, a non-classical MHC class I molecule with immunosuppressive properties. HLA-G interacts with inhibitory receptors such as ILT-2, ILT-4, and KIR2DL4, modulating immune responses. In SLE, aberrant HLA-G expression on immune cells, abnormal levels of soluble HLA-G in serum, and disrupted tissue-specific expression suggest impaired immune checkpoint control. These abnormalities contribute to immune dysregulation and the loss of tolerance, sustaining chronic autoimmunity. Understanding trogocytosis-mediated modulation of HLA-G may offer novel insights into disease mechanisms and therapeutic targets in SLE. This mini review examines the molecular mechanisms underlying trogocytic HLA-G transfer, characterises the dysregulated trogocytosis pathways observed in SLE patient immune cells, and evaluates the therapeutic potential of targeting these intercellular communication networks for disease management. The present review encompasses mechanistic studies of trogocytosis regulation in disease-relevant immune cell populations, analysis of HLA-G transfer kinetics and functional consequences, and assessment of pharmacological interventions that can modulate trogocytic activity to restore immune homeostasis and reduce disease activity in lupus patients, potentially offering novel precision medicine approaches for this heterogeneous autoimmune disorder.